Построение автоматной модели обучения в компьютерных обучающих средах - Ходаковский, Н.И.; Кузьменко, Б.В. (Управляющие системы и машины, 2016)
Созданы новые обучающие технологии, предоставляющие возможность достижения их высокого интеллектуального уровня путем использования компьютерных обучающих сред. На основе специально разработанной модели можно создать решатель математических задач лучше и быстрее человека. Компьютер использует отфильтрованный арсенал готовых форм, приемов и способов решений математических задач, а интеллектуальные ассистенты способствуют созданию упражнений и решению задач. Створено нові навчальні технології, надається можливість досягнення їх високого інтелектуального рівня шляхом використання комп'ютерних навчальних середовищ. На основі спеціально розробленої моделі можна створити вирішувач математичних задач краще і швидше людини. Комп'ютер використовує відфільтрований арсенал готових форм, прийомів і способів розв'язання математичних задач, а інтелектуальні асистенти сприяють створенню і розв'язанню задач. The achievement of high intellectual level for new educational technologies through the use of computer learning environments can be created. Based on a special developed model knowledge representation and procedures for the withdrawal of these new facts solver of mathematical problems that solves them better and faster than a human can be simulated. The carefully selected, filtered and specially organized arsenal of ready-made forms, techniques and methods of solving mathematical problems computer was used. The offered automata models of student and teacher, are capable to interact with each other through the space formal educational material and using intelligent assistants machines help to create the exercises and solve the problems without the programming procedures. The tools of automatic correction of the individual strategies and the possibility of transferring student model formed by a teacher at the personal contacts in the educational computing environment approach is proposed. The construction of educational technology based on the computer learning environments for automata models of student and teacher, who interact with each other through the space of educational material in the form of formalized information marked trees is used. The intelligent assistants in creation the exercises and the problem solving can be used.